The Importance of Mastering Punctuation - Rahma Rizki Nasution; Risyda Luthfiah; Abdul Rafi Alrasyid; Irfansyah (Rahis Cendekia Indonesia, 2024)
This study aims to the importance of Punctuation behind the misuse of punctuation to help in writing and reading. Although often considered ordinary, the use of proper punctuation can effect the way of reading and understanding text. With various types of punctuation such as periods, commas, question marks, exclamation marks, hyphens, quotation marks, and quotation marks. On the other hand, understanding the correct punctuation can facilitate the reading flow and emphasize the reading delivered. In addition, that understanding punctuation is important for academic writing, book, and in everyday communication. The mastery of correct punctuation has an influence on the quality of writing, and makes it easier for readers to follow has author’s train of thought. Mastery of punctuation is a skill to make writing clear, effective, easy to understand, and able to express oneself when reading it.